1999
DOI: 10.1034/j.1398-9995.1999.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic rhinitis and contact urticaria caused by bishop's weed (Ammi majus)

Abstract: Bishop's weed (Ammi majus) has been known to induce toxic phytophotodermatitis. We now describe IgE-mediated rhinitis and contact urticaria caused by exposure to bishop's weed in a 31-year-old atopic female florist. A skin prick-prick test with bishop's weed flowers gave an 8-mm wheal, and the bishop's weed-specific IgE level in the patient's serum was 9.7 PRU/ml (RAST class 3). In an immunoblotting experiment with the patient's serum, nine IgE-binding protein bands with the molecular weights 19, 34, 39-41 (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Table 2 gives a list of the proteins having caused CU and/or PCD of the immunological type. For references see the report of Janssens et al (4), to which more publications have been added (6, 7, 10–93).…”
Section: Causesmentioning
confidence: 99%
“…Table 2 gives a list of the proteins having caused CU and/or PCD of the immunological type. For references see the report of Janssens et al (4), to which more publications have been added (6, 7, 10–93).…”
Section: Causesmentioning
confidence: 99%
“…Hundreds of plants have caused type I all_ergy (1). Occupational contact urticaria (CU) from plants is also often reported (1), but it is less often attributed to decorative houseplants (1–19). We present a patient with occupational CU from weeping fig (2, 4, 5, 10), spathe flower (7, 10, 11), and yucca.…”
mentioning
confidence: 99%
“…The usage of oral khella as a therapy is not as safe as it might sound and limited by its potential cytotoxicity. [24][25][26][27][28] In humans, two studies have been conducted; the first investigated the utilization of oral khellin to reduce blood lipids and the second studiedthe effects of khellin in vitiligo. 24,25 Researchers observed that gastro-intestinal side-effects were observed frequently (29% of patients in the vitiligo study) and, elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were also reported during therapy (7% to 14%).…”
Section: Discussionmentioning
confidence: 99%